Simultaneous Fast Deformation and Solidification in Supercooled Liquid Gallium at Room Temperature1 . Issue 8 (18th May 2017) - Yu, Zhenwei W.; Chen, Yuchen C.; Yun, Frank F.; Wang, Xiaolin L.
Abstract : The authors demonstrate that it is possible to transform a supercooled liquid metal at room temperature into a variety of shapes in solids by combined liquid metal deformation and induced crystallization from the supercooling state. The authors discover that both reversible deformation and irreversible deformation can be achieved simultaneously for supercooled liquid gallium in alkaline or acid electrolytes by using electrodes that are non‐wetted or wetted with liquid gallium, respectively. Our findings on the simultaneous deformation and solidification offer a novel approach to controlled patterning and solidification of supercooled liquid gallium at room temperature. Abstract : Controlling the shape of liquid metals is still a big challenge. Simultaneous deformation and solidification of supercooled liquid gallium is discovered by using an electric field in alkaline or acid electrolytes, which offer a novel approach to controlled patterning and solidification of supercooled liquid gallium at room temperature.